Is there Room for Belief in Judaism? Two German Jewish Thinkers Debate Dogma in 1834 - Kohler, George Y. (Jewish Thought, 2019)
This paper traces the arguments in an 1834 philosophical debate between R. Moritz Freystadt (1810-1870) and the Maimonides scholar Simon B. Scheyer (1804-1854) on the question of whether Judaism possesses dogmas. While Freystadt proposed the re-introduction of Maimonides’ articles of faith into the Jewish religion after the Kantian abolition of all secure belief in the absolute as a form of “reasonable faith,” Scheyer argued that the only Jewish dogma was the divinity of the Pentateuch. For Freystadt, Kant had for all eternity refuted the possibility of religious metaphysics and Judaism had thus to rely on postulates of practical, that is, moral reason for its theological survival. Scheyer, in contrast, upheld the belief in a philosophical Messiah who would eventually contradict Kant and return objectivity to faith. In the meantime, according to Scheyer, the revealed nature of Torah dogmatically authorized both its ceremonial and its philosophical messages. In this sense, the debate anticipated much of the later scientific analysis of the leading scholars of the Wissenschaft des Judentums regarding the emergence and function of dogma and religious authority in Judaism.